2017
DOI: 10.1017/s1431927617007371
|View full text |Cite
|
Sign up to set email alerts
|

In vivo formation of Ce-phosphate Nanoparticles following Intratracheal Instillation of CeCl3: Subcellular sites, Nanostructures, Precipitation Mechanisms and Nanoparticle 3D-Alignment

Abstract: We demonstrate the in vivo formation of nano-particulate Ce-containing structures in lungs instilled with 5 mg/kg CeCl3 using high resolution electron microscopy (HRTEM), energy loss spectroscopy (EELS), and elemental mapping (EDS). The observed high lung retention of Ce after instillation of CeCl3 (75-92% retained at 28 days) is unexpected since metal ions are usually readily transported across the air-blood barrier. The binding of cerium ions to lung constituents has been suggested [1], and the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Although nanoceria may act as a phosphatase to release phosphate, other regions where nanoceria undergoes greater bioprocessing/solubility, such as inside the liver (Graham et al 2014), may favor ion transport over phosphate precipitation. The formation of Ce-phosphate precipitates that form from available metal ions in tissue was previously demonstrated (Berry et al 1997;Graham, Wang, et al 2017) and is independent of nanoceria's phosphatase mimetic activity, suggesting there are several pathways to form Ce-phosphate precipitates. We suggest that Ce-phosphate nanoneedle formation may counteract the toxicity caused by free Ce ions derived from dissolving (bioprocessing) nanoparticles.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Although nanoceria may act as a phosphatase to release phosphate, other regions where nanoceria undergoes greater bioprocessing/solubility, such as inside the liver (Graham et al 2014), may favor ion transport over phosphate precipitation. The formation of Ce-phosphate precipitates that form from available metal ions in tissue was previously demonstrated (Berry et al 1997;Graham, Wang, et al 2017) and is independent of nanoceria's phosphatase mimetic activity, suggesting there are several pathways to form Ce-phosphate precipitates. We suggest that Ce-phosphate nanoneedle formation may counteract the toxicity caused by free Ce ions derived from dissolving (bioprocessing) nanoparticles.…”
Section: Discussionmentioning
confidence: 86%
“…The high retention of Ce (75–92% at 28 days) in the lung after Ce-ion instillation was unexpected. Follow-up HRTEM and EELS revealed that in vivo formation of Ce phosphates had occurred (Graham, Wang, et al 2017). Ce-phosphate precipitation observed in the spleen in the current study also requires a source of Ce ions, which we suggest is a result of the in vivo breakdown and dissolution of nanoparticles in the liver (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation